Social implications of schooling: Knowledge, pedagogy and consciousness - Pathak, Avijit (Delhi Aakar books, 2025)
The beginning of the book in quite captivating. Anyone with little knowledge of sociology would immensely benefit from this book, if they want to delve deeper into questions pertaining the interplay between school and society. (Some typical sociology terms do require looking up on the internet).Also, the fact that the book is written from Indian perspective, is a great help in contextualizing one's understanding of Indian education system. The institutions that Prof Pathak mentions in the book, he himself has been closely associated with them, that is why he can bring about the real picture in it's entirety and not only as a neutral/outside researcher.
Keywords: Schooling; Life at school; Education